PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KURIR PT SICEPAT EKSPRES CABANG KRAMAT JATI JAKARTA TIMUR - Rezky Wahyuni (2021)
This study is a quantitative study into the impact of job motivation and satisfaction on employee performance. The sample used in this study were couriers of PT. SiCepat Ekspres Cabang Kramat Jati East Jakarta where researchers used a saturated sample of 35 couriers. Data collection is done via google form. The path analysis method was employed for the analysis, and data processing was done with smartPLS 3 at a significant level of 5%. (0.05). The test found that (1) work motivation has a significant effect on courier performance, (2) work satisfaction has a significant effect on courier performance, and (3) work motivation and work satisfaction have a significant effect on courier performance at the same time. Work motivation and job satisfaction have an impact on performance by 87.9%. Keywords: work motivation, work satisfaction, and performance.